Chemical investigation of Pseudarthria viscida root by GC-MS analysis - Muthukrishnan, Suriyavathana; Thinakaran, Rajan (Pharmacognosy Communications)
This study was carried out to analyze the active constituents from Pseudarthria viscida roots using Gas Chromatography-Mass Spectrometry. The chemical composition of the methanolic extract of Pseudarthria viscida was investigated using Perkin-Elmer Gas Chromatography-Mass Spectrometry. Mass spectra of the compounds found in the extract were matched with the National Institute of Standards and Technology (NIST) library. This analysis revealed that Pseudarthria viscida root contains eighteen chemical constituents. The major chemical constituents are 3-O-Methyl-d-glucose (61.33%), n-Hexadecanoic acid (12.66%), Oleic acid (7.93%) and 9, 12- Octadecanoic acid (4.88%) This is the first report of identification of active constituents from the root of Pseudarthria viscida by GC-MS.
Keywords: Pseudarthria viscida; GC-MS analysis; chemical components